DNA vaccine targeting betacoronavirus spike protein blocks neuroinvasion and neuroinflammation in swine via dual antiviral-immunomodulatory action - Huabo Yu; Junchao Shi; Guoce Fu; Zezhao Cao; Ruizhao Qiu; Tianqi Zhao; Jing Zhang; Yungang Lan; Jiyu Guan; Kui Zhao; Feng Gao; Wenqi He; et al. (npj Vaccines)
Abstract Porcine hemagglutinating encephalomyelitis virus (PHEV), a neurotropic betacoronavirus, causes fatal neurological disease in piglets, yet no licensed vaccines exist. Here, we developed a DNA vaccine encoding the receptor-binding domain (RBD) of PHEV spike protein fused to IgG1 Fc, adjuvanted with GEL01 (RBD + GEL01). Immunization in mice and piglets elicited robust neutralizing antibodies (titers up to 1:446 and 1:147, respectively) and Th1-biased cellular immunity. The vaccine restricted viral neuroinvasion, reducing brain viral loads by >90% and confining PHEV to discrete olfactory and cortical regions. Vaccinated animals exhibited preserved motor coordination, cognitive function, and minimal neuropathology. Transcriptomic analysis revealed suppression of proinflammatory mediators (e.g., Cxcl2, Saa3) and enhanced neural repair pathways, highlighting dual virological control and immunomodulatory mechanisms. As the first DNA vaccine against PHEV, the RBD + GEL01 candidate offers scalable protection against neurotropic coronaviruses by dual antiviral-immunomodulatory strategy, underscoring its potential to mitigate economic and zoonotic risks.